Konflik Batin Tokoh Utama Novel Lakuna Karya Khrisna Pabichara Dalam Kajian Psikoanalis Sigmund Freud - Putri Anggiani; Imas Juidah; Agus Nasihin (Stilistika: Jurnal Pendidikan Bahasa dan Sastra, 2026)
This study examines the inner conflict of the main character in the novel Lakuna by Khrisna Pabichara through a literary psychology approach with Sigmund Freud's psychoanalytic theory. The method used is descriptive qualitative with documentation study techniques in the form of intensive. reading, note-taking, and identification of relevant quotes that represent inner conflict. The results of the study show: 1) The main character experiences conflict between subconscious drives, demands of reality, and moral values. 2) The dynamics of the id, ego, and superego are contradictory, thus influencing the character's attitudes and decisions in facing life's problems. 3) The conflict is more dominant in the id aspect because of unfulfilled desires and hopes, causing ongoing psychological tension. The symbolization of this inner conflict emphasizes the character's inability to balance drives and demands of life. In conclusion, the novel Lakuna reveals the psychological complexity of the main character and demonstrates the effectiveness of Freud's psychoanalysis in describing the depth of character and the meaning of the story.